Meningkatkan Kemampuan Bernalar Kritis Dan Prestasi Belajar Melalui Discovery Learning Berbantuan Video Materi Dialog Antarumat Beragama Fase F SMKN 2 Magelang - Yustina Kristiati (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education in Indonesia has experienced many developments from year to year with various models, different methods, and curriculum changes according to the needs of the times. One of them is Merdeka Belajar. Through Religious Learning, students are encouraged to actively communicate, be creative, explore, be skilled at reflection and dare to express their opinions. In this learning, students are also given the opportunity to carry out a project to strengthen the Pancasila student profile which includes six dimensions. In this classroom action research, the researcher focuses on the dimensions of critical reasoning. With critical reasoning skills, students are expected to be able to identify, solve problems, make the right decisions to overcome various problems and be able to see things from various perspectives and be open. SMK Negeri 2 Magelang is a favorite school with many achievements. Because it is a vocational school, learning is more focused on productive (vocational) subjects so that general subjects (adaptive normative) receive less attention from students. Based on the results of observations, it was found that there was a decline in student learning achievement in PAK learning. Based on these problems, researchers are trying to design the learning process to be more varied and interesting. One of the learning models implemented is video-assisted Discovery Learning. This research was conducted at SMKN 2 Magelang Phase F class XII with the research variables learning achievement and critical reasoning. The aim of this research is to determine the application of the video-assisted Discovery Learning learning model which can improve learning achievement and determine critical reasoning abilities in class XII PAK learning at SMK Negeri 2 Magelang. Data collection techniques using observation sheets for critical reasoning variables and tests for learning achievement variables. Data from observations and test results were scored and processed and then presented descriptively. The research results show an increase in accordance with the expected achievement targets. The results of learning achievement in cycle II show an increase, this can be seen from the test results which reached the category from 0% to 33.3%, the proficient category from 16.7% to 50% and the adequate category from 50% to 16.7% and new categories are developing 33.3% to 0%. The results of critical reasoning ability also increased, the proficient category was 33.3%, which was previously 0%, the proficient category was 66.7%, which was previously 50%. This increase shows that the video-assisted discovery learning model is proven to be able to improve students' learning achievement and critical reasoning abilities.